Autophagy: A Role in the Apoptosis, Survival, Inflammation, and Development of the Retina - Lin, Wen; Xu, Guoxing (Ophthalmic research, 2019)
Autophagy is a lysosomal degradation process that maintains cellular homeostasis by removing dysfunctional organelles and unfolded proteins. Increasing evidence has shown that autophagy proteins are involved in retinal physiology and pathology and that defective autophagy contributes to retinal degeneration. In retinal diseases, autophagy plays a dual role: promoting retinal cell survival and death. Autophagy at a normal level helps retinal cells defend themselves against harmful stress; however, excessive autophagy results in retinal deterioration. Both synergistic and antagonistic roles of autophagy and apoptosis in the retina have been reported in the literature. In this review, we summarize the roles of autophagy in the development of the retina and retinal diseases. This review highlights the importance of autophagy in retinal diseases, and targeting autophagy may provide a new therapeutic approach for retinal diseases.